The management of gastric volvulus in elderly patients. (2016) - Zuiki, Toru; Hosoya, Yoshinori; Lefor, Alan Kawarai; Tanaka, Hiroyuki; Komatsubara, Toshihide; Miyahara, Yuzo; Sanada, Yukihiro; Ohki, Jun; Sekiguchi, Chuji; Sata, Naohiro
Highlights: Endoscopy is necessary for management of gastric volvulus. Endoscopic reduction is effective as first aid for gastric volvulus. Endoscopic gastropexy is available for gastric volvulus in elderly patients. Laparoscopic gastropexy can be an alternative to hernia repair in poor condition. Abstract: Introduction: Gastric volvulus is torsion of the stomach and requires immediate treatment. The optimal treatment strategy for patients with gastric volvulus is not established, because of significant variations in the cause and clinical course of this condition. Presentation of cases: We describe our experience with six elderly patients with gastric volvulus caused by different conditions using various approaches. This includes two patients managed with endoscopic reduction, followed by endoscopic or laparoscopic gastropexy. Discussion: Endoscopy is a necessary first step to determine the optimal treatment strategy, and endoscopic reduction is often effective. The indications for surgical repair of gastric volvulus depend on the patient's overall condition, and several options are available. In some elderly patients with severe comorbidities, major surgery may have an unacceptably high risk. We propose a novel treatment strategy for gastric volvulus in the elderly and a review of the literature. Conclusion: Early endoscopy is necessary in patients with gastric volvulus. Endoscopic or laparoscopic gastropexy may be adequate therapy in selected elderly patients.